JOB STRESS MANIFESTATIONS AMONG EDUCATIONAL PERSONNEL IN RAJAMANGALA UNIVERSITY OF TECHNOLOGY LANNA, CHIANG RAI CAMPUS - Pichedboonkiat, Sirichom; Chosri, Rachen (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This study aimed to study 1) job stress manifestations 2) the level of job stress manifestations, and 3) factors affecting job stress of educational personnel in Rajamangala University of Technology Lanna, Chiang Rai campus. Data were gathered using questionnaires. Descriptive and inferential statistics, such as frequency, percentage, mean, and standard deviation were used in analyzing the data. Result revealed that as following 1) The job stress manifestations of the RMUTL, Chiangrai campus educational personnel were found to have high stress in psychological characteristics ( =3.34), based on indicators studied, and perceived their work environment to be high ( =3.29) 2) The level of job stress manifestations of the RMUTL, Chiangrai campus educational personnel revealed that most of them had very low physical and behavioral stress manifestations. ( =2.00), ( = 1.80) 3) Factors affecting job stress of educational personnel in Rajamangala University of Technology Lanna, Chiang Rai campus revealed that most of them had a high stress on three work environment which were organizational factors ( =3.29), job factors ( =3.10), and work group factors. ( =2.90)